Kaukaz Południowy po upadku ZSRR – próby transformacji i konflikty etniczne - Fedorowicz, Krzysztof (Wydawca Towarzystwo Nauki i Kultury „Libra”, 2017)
W niniejszym artykule autor analizuje procesy kształtowania się politycznych systemów w państwach Kaukazu Południowego. Wskazuje przy tym na patologiczne zjawiska funkcjonujące w elitach władzy oraz w systemach politycznych tych państw. Analizie poddane zostały także konflikty w Górskim Karabachu, Abchazji i Osetii Południowej, które nadal dominują w życiu politycznym Armenii, Azerbejdżanu i Gruzji. Są podstawą ideologii i programów politycznych elit walczących o władzę, a także znacząco wpływają na styl przywództwa. W politycznej walce znaczącą rolę odgrywały elity wojskowe, które szybko awansowały na szczyt władzy. Autor próbuje wyjaśnić, jak konflikty w Górskim Karabachu, Abchazji i Osetii Południowej wpływają na proces transformacji ustrojowej państw regionu. Kolejnym aspektem analizy jest odpowiedź na pytanie, jak tradycja, kultura, psychologia, styl życia i interesy politycznych elit Armenii, Azerbejdżanu i Gruzji wpływają na rezultaty pokojowego uregulowania konfliktów.

The Author analyses proces of the formation of political regimes in Southern Caucasus. He points to the pathological phenomena in the functioning of power elites and political regimes of those states. The Author analyses the influence of conflict in Nagorno Karabakh, Abkhazia and South Ossetia on the domestic and foreign policy of Armenia, Azerbaijan and Georgia. He proves that the described conflict for many years dominated in the political life of this country and was a basis of the ideology and the programs of elites struggling for power. In the struggle of the elites, the military elites played the main role, while being an important path to advancement to the peaks of power. The author tries to explain the influence of the Karabakh, Abkhazia and South Ossetia question on political transformation of the states in conflict. Another important thread of the analysis is to search answers to the question, how tradition, culture, psychology, life styles and political interests of elites in Armenia, Azerbaijan and Georgia affect the course and the effects of a peacemaking process aimed solving the Karabakh, Abkhazia and South Ossetia.
South Caucasus after the collapse of the USSR – and the attempted transformation of ethnic conflicts
Keywords: Kaukaz Południowy; South Caucasus; transformacja; konflikty etniczne; South Caucasus; transformation; ethnic conflicts